Power utility re-regulation in East European and CIS transformation countries (1990-1999) : an institutional interpretation - Christian R. von Hirschhausen; Petra Opitz (Deutsches Institut für Wirtschaftsforschung (DIW), 2001)
This paper analyzes the process of power utility re-regulation in Eastern Europe and the CIS during the decade of systemic transformation (1990-1999); in particular, it explores reasons why early attempts to introduce competition-oriented reform models have not succeeded. We discuss advantages and disadvantages of various reform models from an institutional economic perspective. The approaches to and results of power sector reform in Eastern Europe are assessed; quantitative indicators are wholesale and retail prices, cost coverage ratios, investment levels, and the degree of unbundling and privatization. The paper concludes that a gradual approach to reforms may have been appropriate for the first years of systemic transformation, but that today, ten years later, there is no reason to delay market-oriented reforms any longer. – – Der Beitrag untersucht die Re-Regulierung der Stromwirtschaften in den osteuropäischen Transformationsländern zwischen 1990 und 1999; insbesondere wird geprüft, warum frühe marktorientierte Reformansätze gescheitert sind. Nach einem Vergleich alternativer Reformmodelle werden der Prozess und die Ergebnisse der Re-Regulierung analysiert; quantitative Indikatoren sind die absoluten und relativen Preise, Kostendeckungsgrade, die Höhe der Investitionen und da Ausmaß der Liberalisierung und Privatisierung. Die vorliegende Evidenz legt nahe, dass aufgrund technischer und institutioneller Schwierigkeiten eine umgehende Marktöffnung nicht möglich war; andererseits gibt es heute, 10 Jahre später, keinen Grund mehr, die Liberalisierung und Privatisierung der Stromwirtschaft weiter zu verzögern.
Keywords: L94; P23; O17; 330; Strom; Transformation; Osteuropa; Institutionen; Power sector; institutions; transition; Eastern Europe; Elektrizitätspolitik; Regulierung; Übergangswirtschaft; Institutionalismus; Transaktionskosten; Osteuropa; GUS